ECM-enriched alginate hydrogels for bioartificial pancreas: an ideal niche to improve insulin secretion and diabetic glucose profile. Issue 4 (October 2019) - Crisóstomo, Joana; Pereira, Ana M; Bidarra, Sílvia J; Gonçalves, Ana C; Granja, Pedro L; Coelho, Jorge FJ; Barrias, Cristina C; Seiça, Raquel
Introduction: The success of a bioartificial pancreas crucially depends on ameliorating encapsulated beta cells survival and function. By mimicking the cellular in vivo niche, the aim of this study was to develop a novel model for beta cells encapsulation capable of establishing an appropriate microenvironment that supports interactions between cells and extracellular matrix (ECM) components. Methods: ECM components (Arg-Gly-Asp, abbreviated as RGD) were chemically incorporated in alginate hydrogels (alginate-RGD). After encapsulation, INS-1E beta cells outcome was analyzed in vitro and after their implantation in an animal model of diabetes. Results: Our alginate-RGD model demonstrated to be a good in vitro niche for supporting beta cells viability, proliferation, and activity, namely by improving the key feature of insulin secretion. RGD peptides promoted cell–matrix interactions, enhanced endogenous ECM components expression, and favored the assembly of individual cells into multicellular spheroids, an essential configuration for proper beta cell functioning. In vivo, our pivotal model for diabetes treatment exhibited an improved glycemic profile of type 2 diabetic rats, where insulin secreted from encapsulated cells was more efficiently used. Conclusions: We were able to successfully introduce a novel valuable function in an old ally in biomedical applications, the alginate. The proposed alginate-RGD model stands out as a promising approach to improve beta cells survival and function, increasing the success of this therapeutic strategy, which might greatly improve the quality of life of an increasing number of diabetic patients worldwide.